DEPENDENCE STRUCTURE AMONG CRYPTOCURRENCIES - Raza, Ahmad; Javed, Naeem; Aftab, Rabeea; Shafique, Anum; Batool, Farwa (The journal of contemporary issues in business and government, 2021)
This research paper studies the dependence structure among cryptocurrencies. In this study, secondary data of five cryptocurrencies is used for five years (2015-2020), which was gathered from the coin market cap website. On the basis of most market capitalization, five cryptocurrencies,bitcoin, ethereum, tether, ripple and lite coin are selected. Descriptive statistics, copulas methodology, spearman and kendal tau correlation are the techniques used for hypothesis testing. This study finds that there is dependence among log-returns of selected five cryptocurrencies except for three pairs; “Bitcoins and Ethereum, Bitcoins and Litecoin, Ethereum and Litecoin”. All other combinations showed results that there is dependence among cryptocurrencies. Value of akaike information criterion is used to choose the copula that best fit the model. Results show that t- student copula is the best fit model withsymmetric tail dependence. All findings are helpful for investors, researchers, financial analysts and policy makers for future predictions.